Clinical Efficacy of Yoga Practices in the Management of Polycystic Ovarian Syndrome: Insights from a Single-arm Pilot Trial - Singh, Shalini; Arya, Vedpriya; Kumar Mishra, Rajesh; Kumar Rajput, Satyendra (International Research Journal of Ayurveda & Yoga, 2025)
Polycystic ovarian syndrome (PCOS) is a prevalent endocrine disorder among reproductive-age women, characterized by hormonal, metabolic, and psychological disturbances. Conventional therapies predominantly provide symptomatic relief but often fail to address the multifactorial nature of the condition. This single-arm, 12-week pilot trial investigated the impact of a structured yoga program on clinical, hormonal, metabolic, and psychological outcomes in women with PCOS. The study was conducted at the Yoga and Shatkarma Department, Patanjali Yogpeeth, Haridwar, and included 49 women diagnosed with PCOS according to the Rotterdam criteria. Participants underwent a yoga intervention comprising specific asanas (Baddha Konasana, Bhujangasana, and Naukasana), pranayama techniques (Anulom Vilom, Bhramari, and Kapalbhati), and relaxation practices. Primary outcomes included menstrual cycle regularity, hormonal profiles (testosterone, luteinizing hormone [LH], follicle-stimulating hormone [FSH]), and metabolic indicators (body mass index [BMI], waist-to-hip ratio, insulin sensitivity). Secondary outcomes assessed psychological well-being, including stress and anxiety. Statistical analyses were performed using unpaired t-tests and receiver operating characteristic curve evaluation. Following the intervention, participants demonstrated improvements in menstrual regularity, acne, and hirsutism. Significant reductions in testosterone levels and normalization of the LH/FSH ratio were observed. Metabolic outcomes showed improved insulin sensitivity, reduced BMI, and better weight control. Psychological measures indicated reductions in stress and anxiety scores. These results suggest that yoga may provide multidimensional benefits in PCOS management, targeting endocrine, metabolic, and psychological domains. While the findings highlight yoga as a safe, cost-effective, and holistic intervention, further randomized controlled trials with larger sample sizes are warranted to establish causal effects and long-term efficacy.